Terremotos profundos na região amazônica (Acre): mecanismos focais e parâmetros de fonte - Leite Neto, Gilberto da Silva (2024)
Deep earthquakes occur at depths greater than 70 km, in the cold core of the subducting lithosphere, where the extreme pressure and temperature conditions should prevent brittle failure. Thus, alternative physical processes are necessary in order to explain the occurrence of these events. At depths exceeding 300 km, earthquakes are attributed to transformational faulting, a mechanism that relies on the presence of a metastable olivine wedge (MOW) in cold slabs. However, these events also occur in warm slabs, such as the Nazca plate, which makes explaining these phenomena even more challenging. This study aims to investigate the generating mechanism in South America by determining focal mechanisms and source parameters for a sequence of 42 deep-focus events in the Amazonian region between Peru and Brazil (2014-2022). To achieve this goal, data from several broadband stations distributed across the continent were utilized, ensuring unprecedented coverage of these events. Initially, focal mechanisms and centroid depths were determined for a total of 28 events (Mw 4.2-7.5) using the Cut-and-Paste method. The mechanisms reveal a predominance of normal faults reflecting a down-dip compression (DDC) regime. Nodal planes, oriented approximately 45º from the axis of maximum compression, indicate the formation of new faults, consistent with transformational faulting. Centroid depths demonstrate a seismic zone confined between 557 and 659 km. These observations suggest that seismicity may result from transformational faulting within a MOW preserved by a colder slab segment attached at depth to a warmer Nazca Plate. Seismic moments, corner frequencies, and radiated energies were determined for 13 events (Mw 4.8-7.4) from P- and S-wave spectra. From these parameters, stress drops (5-90 MPa) and radiation efficiencies (0.1-1.4) were calculated, revealing significant variations. The variability in radiation efficiencies suggests the coexistence of brittle and dissipative ruptures, possibly influenced by the degree of melting in the fault zone and favored by the dehydration of hydrous phases near the source. Thus, this work suggests that deep-focus earthquakes in the region result from the combination of transformational faulting and thermal runaway, the latter involving more or less melting depending on the presence of water near the source.